Enhancing commercialization level of academic research outputs in research university - Khademi, Tayebeh (Penerbit UTM Press, 2015)
The aim of this study was to improve the commercialization level in Universiti Teknologi Malaysia (UTM). For achieving this goal various factors and issues were examined to identify how they affect the procedure of university commercialization. These factors include the role of technology transfer office /center, availability of finance, availability of potential licensee and entrepreneurial orientation (EO) among the university researchers. Among these four factors, this study focused more on EO among academic researchers and its effect on the commercialization rate. This study was based on a qualitative research method and was designed to use a case study approach. For investigating the factors and issues in this study, a total of ten face-to-face interviews were conducted. The respondents were chosen from inventors, researchers, academic entrepreneurs, and Technology Transfer Office staff in UTM. The researcher utilized the content-analysis approach to analyze the data obtained from the semi-structured interviews of the respondents. The results indicated that EO among the university researchers, the role of technology transfer office /center, the availability of potential licensee and availability of finance were significant to the research output commercialization at university. Overall, the most critical factor was availability of finance.